APLIKASI PEMBELAJARAN PRAKTIS ALAT dan MESIN PERTANIAN BERBASISANDROID - Andreas R. Pinontoan; Robert Molenaar; Hildy Wullur (Universitas Sam Ratulangi, 2015)
ABSTRACT Information on agricultural machinery and equipment is required for the development of agricultural technology in Indonesia. Although Indonesia is known as an agricultural country, its agricultural technology is considered less developed compared to many other non-agricultural countries. One reason behind this is the dissemination of information regarding agricultural machinery and equipment still believed asunstructured and fragmented. Advancement in information and communication technology has made easiness for people in accessing information. Android operating system is gaining more and more popularity and its userin Indonesia is growingfast. This research aims to develop an Android based practical learning application on agricultural machinery and equipment. This research was carried out during the month of April 2015 to June 2015 and the resulted application was successfully installed in Android as a 1.8 Mb APK file format. The application was tested on CPU emulator and Andromax smartphone followed by a survey to 16 respondents using questionnaire having 10 questions in it (5 questions for application and 5 other questions for content of application). The respondents, who marked each question with 1=very disagree; 2=disagree; 3=neutral; 4=agree; 5=very agree, consist of 10 university students, 3 university lecturers, 1 representing farmer, 1 consultant in agricultural machinery and equipment, and 1 representingcommon people. Results of the test conclude that this Android application can be implemented as information media to improve awareness of public and university students regarding agricultural machinery and equipment in a quicker and a more efficient way. The application can also help disseminating information regarding agricultural machinery and equipment in a more variety way in order to support the development of agricultural technology in Indonesia.